Management of Pineapple Disease of Sugarcane through Biological Means - Talukder, MI; Begum, F; Azad, MMK (Journal of Agriculture & Rural Development, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Trichoderma harzianum was found an effective antagonist to Ceratocystis paradoxa, the causal organism of pineapple disease of sugarcane. It exhibited a strong antagonism against Ceratocystis paradoxa by overgrowing on it, forming lysed zone and inhibiting its growth. In the present investigation Trichoderma harzianum was found as effective as fungicide (Bavistin 50WP- Carbendazim 50WP) in controlling Ceratocystis paradoxa both in in vitro and in vivo condition. Ceratocystis paradoxa failed to grow on Trichoderma harzianum and Bavistin 50WP treated PDA plates. Trichoderma harzianum and Bavistin treated sugarcane setts showed significantly higher germination (20.34 to 26.17% higher) over control. Trichoderma harzianum and Bavistin treated sugarcane setts showed respectively 40.72 and 62.69% higher yield of cane compared to control. Hence Trichoderma harzianum may be used as bio agent and alternative to Bavistin 50WP (a standard sett treating fungicide of sugarcane) in controlling pineapple disease of sugarcane. Key words: Sugarcane, pineapple disease, biological control. DOI = 10.3329/jard.v5i1.1462 J Agric Rural Dev 5(1&2), 79-83, June 2007